Wajah Pendidikan Islam Persfektif Islam Humanis dan Virtualis - syakban abdul karim (eL-HIKMAH: Jurnal Kajian dan Penelitian Pendidikan Islam, 2021)
Islamic education focuses on civilized moral and intellectual education with the concepts of tarbiyyah, ta'lim, and ta'dib. For this reason, this article examines the face of Islamic education from the perspective of Humanist and virtual Islam by using a literature review research method. Islamic education is not only to ensure happiness in fulfilling the needs in the world but also in the hereafter. Good nature and character and have good morals who are always updating themselves. be a reference of humanist Islam. Humanist and virtual Islam in Islamic education is embodied in learning behavior that is practiced with love so that all its potential develops in an education system based on the Qur'an and As-Sunnah. Islamic education in the virtualist perspective is the crystallization of Islamic adherents of religious values ??in the development of cyberspace. Virtualist Islam is shown by the behavior of the sami'na towards the teachings conveyed through online da'wah. So that religious fanaticism depends on who is portrayed and the choices of Islamic studies in cyberspace. In essence, Islamic education from a humanist and virtualist perspective is an education system that is taught with love through real and virtual interactions.